(untitled) (Scientific journal of the Fergana State University, 2023)
Music lessons are distinguished from other subjects at school by their artistry, fun and evoking figurative experiences. Music has a positive effect on the mental and moral education of my child. And artistic upbringing is its logical content. The internal structure of the music lesson consists of various samples of the history, theory and performance of music - vocal-choral training, music basket, listening to music, Music analysis and literature, playing children’s instruments, performing rhythmic movements. Therefore, it belongs to the mixed lesson type.